2006
DOI: 10.1101/gr.5273806
|View full text |Cite
|
Sign up to set email alerts
|

Comparative isoschizomer profiling of cytosine methylation: The HELP assay

Abstract: The distribution of cytosine methylation in 6.2 Mb of the mouse genome was tested using cohybridization of genomic representations from a methylation-sensitive restriction enzyme and its methylation-insensitive isoschizomer. This assay, termed HELP (HpaII tiny fragment Enrichment by Ligation-mediated PCR), allows both intragenomic profiling and intergenomic comparisons of cytosine methylation. The intragenomic profile shows most of the genome to be contiguous methylated sequence with occasional clusters of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
284
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(290 citation statements)
references
References 43 publications
5
284
0
1
Order By: Relevance
“…The HpaII tiny fragment enrichment by ligation-mediated PCR (HELP) assay was performed as previously described, 29 design name: 100128_HG19_MKF_HELP_ChIP_HX3, design ID: 11291), based on the GRCh37/HG19 assembly of the human genome. Data preprocessing and normalization were performed as previously described.…”
Section: Molecular Mutationsmentioning
confidence: 99%
“…The HpaII tiny fragment enrichment by ligation-mediated PCR (HELP) assay was performed as previously described, 29 design name: 100128_HG19_MKF_HELP_ChIP_HX3, design ID: 11291), based on the GRCh37/HG19 assembly of the human genome. Data preprocessing and normalization were performed as previously described.…”
Section: Molecular Mutationsmentioning
confidence: 99%
“…Genome-wide DNA methylation analysis of the human promoter regions ‫007מ(‬ to 200 bp from the TSS) suggested that the DNA methylation status of a limited number of genes correlated with transcriptional activity (Weber et al 2005(Weber et al , 2007. A HELP assay, another genome-wide study, revealed plurality of T-DMRs within 1 kb in promoter regions, suggesting their involvement in tissue-specific expression (Khulan et al 2006). In our study, D-REAM revealed that T-DMRs are localized at a few kilobases both upstream and downstream of the TSS and that the DNA methylation status of these T-DMRs correlates with the transcriptional activities of the neighboring genes.…”
Section: Correlations Between Expression Levels Of Genes and T-dmrs Imentioning
confidence: 99%
“…Microarray technology for the analysis of DNA methylation has advantages and disadvantages (Khulan et al 2006). When compared with systems using isoschizomers, D-REAM is flexible because it enables selective amplification of DNA fragments digested with any restriction enzyme, e.g., HpyCH4IV and NotI, a methylation-sensitive enzyme with recognition sites without isoschizomers.…”
Section: Correlations Between Expression Levels Of Genes and T-dmrs Imentioning
confidence: 99%
See 1 more Smart Citation
“…The microarray-based high-resolution HELP assay was performed on a total of 39 samples (19 nonsmokers and 20 smokers) (48). A 720K Roche-NimbleGen custom array capturing 117 521 HpaII fragments was used to assay CpG islands, CpG island shores and reference sequence promoters.…”
Section: Help Assaymentioning
confidence: 99%